Holographic cosmology solutions of problems with pre-inflationary cosmology - Nastase, Horatiu [UNESP] (Springer Nature, 2020)
In this paper we describe in detail how to solve the problems of pre-inflationary cosmology within the holographic cosmology model of McFadden and Skenderis [1]. The solutions of the smoothness and horizon problems, the flatness problem, the entropy and perturbation problems and the baryon asymmetry problem are shown, and the mechanisms for them complement the inflationary solutions. Most of the paper is devoted to the solution of the monopole relic problem, through a detailed calculation of 2-loop correlators of currents in a toy model which we perform in d dimensions, in order to extract its leading dependence on geff2=gYM2N/q and find a dilution effect. Taken together with the fact that holographic cosmology gives as good a fit to CMBR as the standard paradigm of Λ CDM with inflation, it means holographic cosmology extends the inflationary paradigm into new corners, explorable only through a dual perturbative field theory in 3 dimensions.
Keywords: AdS-CFT Correspondence; Cosmology of Theories beyond the SM